The earliest stage of Izu rear‐arc volcanism revealed by drilling at Site U1437, International Ocean Discovery Program Expedition 350. (17th February 2020) - Sato, Tomoki; Miyazaki, Takashi; Tamura, Yoshihiko; Gill, James B.; Jutzeler, Martin; Senda, Ryoko; Kimura, Jun‐Ichi
Abstract: The International Ocean Discovery Program Expedition 350 drilled between two Izu rear‐arc seamount chains at Site U1437 and recovered the first complete succession of rear‐arc rocks. The drilling reached 1806.5 m below seafloor. In situ hyaloclastites, which had erupted before the rear‐arc seamounts came into existence at this site, were recovered in the deepest part of the hole (∼15–16 Ma). Here it is found that the composition of the oldest rocks recovered does not have rear‐arc seamount chain geochemical signatures, but instead shows affinities with volcanic front or some of the extensional zone basalts between the present volcanic front and the rear‐arc seamount chains. It is suggested that following the opening of the Shikoku back‐arc Basin, Site U1437 was a volcanic front or a rifting zone just behind the volcanic front, and was followed at 9 Ma by the start of rear‐arc seamount chains volcanism. This geochemical change records variations in the subduction components with time, which might have followed eastward moving of hot fingers in the mantle wedge and deepening of the subducting slab below Site U1437 after the cessation of Shikoku back‐arc Basin opening. Abstract : The IODP Expedition 350 drilled between two Izu rear‐arc seamount chains at Site U1437, which reached 1806.5 m below seafloor and recovered in situ hyaloclastites of ∼15–16 Ma. The composition of the oldest rocks shows affinities with volcanic front. This geochemical change records variations in the subduction components with time, which might have followed eastward moving of hot fingers in the mantle wedge and deepening of the subducting slab below Site U1437 after the cessation of Shikoku Basin opening.